Developing Entrepreneurship Characters through Community Service Program - Aliyyah, Rusi Rusmiati; Sugiarti, Reggy; Anjani, Zahra; Sapaah, Aini Nur (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2018)
Community service aims to provide solutions to solve the problem of the residents of Cipayung Girang Village, Bogor Regency, which is given through a sectoral approach as a downstream of research and teaching on the entrepreneurial aspects of the community. The entrepreneurial culture is an essential part of social activities in society because it is a benchmark in measuring the income of citizens. Program identification is carried out through a field survey to analyse the service program then. Data is collected through interviews, observation, and documentation. The results of community service show that there is an increase in the character of community entrepreneurship. The creativity of the people's business has developed through the efforts of socialisation, counselling and entrepreneurship workshops. The results of community efforts in the form of cassava muffins, banana yogurt , crispy cassava, banana peel (setup) jam, banana nectar, and sweet potato cork eggs as well as woodworking into ready-to-eat processed with local agricultural products, were exhibited at community service workshops by promoting products of the people's business to the people of Bogor.